PENGARUH SULFAT PADA KEKUATAN BETON YANG MENGGUNAKAN LIMBAH BATU BARA SEBAGAI BAHAN PENGGANTI SEMEN - Randy Setiawan; Fera Lestari; Dian Pratiwi (Universitas Bandar Lampung, 2017)
Many industries meet the electricity needs by establishing their own Steam Power (power plant) coal-fired. Burning coal produces waste in the form of fly ash (fly ash) in very much. Therefore, this study uses fly ash concrete-making materials such as cement replacement. In this research, test the strength of normal concrete and geopolymer concrete cube measuring 15 x 15 X15 cm 3. Materials used in this study were sand (fine aggregate), gravel / split (coarse aggregate), water, NaOH solution, fly ash / fly ash, cement, alkaline activator is a solution of sodium silicate, sodium hydroxide, sulfate and water. Measurement of compressive strength of geopolymer concrete and ordinary concrete with each of treated water tidal sulfate (treatment on ferrocement tanks) and untreated water tidal sulfate at daily intervals to the 1st, 7th, 14th, 21st , to-28. Each daily intervals used 5 pieces of concrete. Analysis of the data used is the ratio between the compressive strength of ordinary concrete and geopolymer. Conclusion of this research is fly ash can be used instead of 100% cement to mix concrete. Sulfuric affect the strength of normal concrete. While on geopolymer concrete sulfate solution has not yet affected the strength of concrete.